APLIKASI DESIGN OF EXPERIMENT DALAM PROSES OPTIMASI MOISTURE CONTENT PADA PENGERINGAN KAYU MENGGUNAKAN KILN DRYING - Sukirman Sukirman (Faculty of Industrial Technology Universitas Islam Indonesia, 2014)
The utilization of wood for furniture industry require special handling such as reduction of the content of water in order to produce a quality product. Drying the means used to reduce the water content results in a timber. The purpose of this is to predict the value pebelitian water content (moisture content) on the wood drying kiln wood drying process. This prediction is required to determine the quality of the wood to be processed as well about half finished products and finished products. Besides the impact on the moisture content of wood durability. Thus the current drying in an oven (kiln) required proper variable settings. Design of Experiment (DOE) can be used to predict the exact value of moisture content and quickly with low cost. In this study, the values obtained optimum moisture content 17.3%, with the optimum factor levels for temperature = 50 ° C, the cross-sectional area = 415 cm2 object, relative humidity = 80%, time = 15 days. Improved performance is achieved up to 12:57% compared with the previous arrangement.